Managing information gaps on caregivers of psychotic patients in primary health settings of Yogyakarta, Indonesia - Carla Raymondalexas Marchira; Warih Andan Puspitosari; Ida Rochmawati; Siti Mulyani; Irwan Supriyanto (Tabriz University of Medical Sciences, 2018)
Background: Information gaps hinder the management of psychotic patients. Incorporating mental health services into primary care might solve the problem. Health workers can betrained to provide psycho-education for caregivers of psychotic patients.Methods: This study was a two stage experimental study. In the first stage, 43 health workers were trained to provide a psycho-education for caregivers of psychotic patients. Next, 10 health workers were selected to provide the psycho-education. Participants were family caregivers of psychotic patients (n = 113) randomly assigned to control and intervention groups. Pre- andpost-tests were conducted to assess the results. Statistical analyses were conducted using paired t tests and analysis of covariance (ANCOVA).Results: The intervention group scored higher for Knowledge of Psychosis at post-test. Both groups showed significant increase of knowledge (paired t tests: P<0.001; P<0.001; respectively) and the increases were not significantly different between the groups (ANCOVA: P=0.057).Conclusion: Psycho-education was applicable in primary care settings. Training primary care health workers is a feasible method to address information gaps in the management of mental health problems.